On various parameters of Zq-simplex codes for an even integer q - Chella Pandian, P.; Durairajan, C. (Algebra and Discrete Mathematics, 2015)
In this paper, we defined the Zq-linear codes and discussed its various parameters. We constructed Zq-Simplex code and Zq-MacDonald code and found its parameters. We have given a lower and an upper bounds of its covering radius for q is an even integer.